TIPOLOGI KURIKULUM - Wasiah Wasiah (ADIBA : JOURNAL OF EDUCATION, 2022)
This paper aims to explain the typology of curriculum, curriculum based on content, curriculum based on development models, curriculum based on real expectations, curriculum based on structure and learning materials, and curriculum based on the scope of use. Curriculum is an important part of an educational process. Because an education without a curriculum will look irregular. In addition, the curriculum is one of the tools to achieve educational goals, and is also used as a guide in the implementation of the teaching and learning process at various types and levels of schools. The purpose of the curriculum is to educate students or students in the world of education in order to guide and educate students to become intelligent, morally knowledgeable, responsible, innovative creative individuals, and able to enter into social life. Education is a process of changing human behavior both related to aspects of attitudes, skills and knowledge.